Intercomparison of Calculated Incident Power Density and Temperature Rise for Exposure From Different Antennas at 10–90 GHz - Kun Li (IEEE, 2021)
Recently, international exposure guidelines/standards for human protection from electromagnetic fields were revised. For frequencies between 6–300 GHz, the permissible incident power density is defined as the reference level, which is derived from a new metric “absorbed/epithelial power density” based on thermal modeling. However, only a few groups computed the power density and the resultant temperature rise at frequencies greater than 6 GHz, where their exposure conditions were different. This study presents the first intercomparison study of the incident power density and the resultant temperature rise in a human body exposed to different frequency sources ranging from 10 to 90 GHz. This intercomparison aims to clarify the main causes of numerical calculation errors in dosimetry analyses through objective comparison of computation results from six organizations using their numerical methods with various body and antenna models. The intercomparison results indicate that the maximum relative standard deviation (RSD) of peak spatially averaged incident power densities for dipole and dipole array antennas is less than 22.1% and 6.3%, respectively. The maximum RSD of the heating factor, which is defined as the ratio of the peak temperature elevation at the skin surface to the peak spatially averaged incident power density in free space, for dipole and dipole array antennas is less than 43.2% and 41.2%, respectively. The deviations in the heating factors caused by different body models and dielectric/thermal parameters are within 33.1% and 19.6% at 10 and 30 GHz, respectively, when the antenna-to-skin model distance is greater than 5 mm. Under this condition (>5 mm), the deviation in the heating factors caused by different antenna models at 30 GHz does not exceed 26.3%. The fair agreement among the intercomparison results demonstrates that numerical calculation errors of dosimetry analyses caused by the definition of spatially averaged incident power density are marginal.